JAVIER PÉREZ HERRERAS (coord.) - Architecture as Nature. From Geography to Anatomy - Tárrago Mingo, Jorge (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2022)
Javier Pérez Herreras (coord.) Arquitectura como Naturaleza. De la Geografía a la Anatomía / Architecture as Nature. From Geography to Anatomy Zaragoza: Prensas de la Universidad de Zaragoza, 2021. 134 pp. Softcover. Language: Spanish and English. 19 € ISBN 978-84-1340-249-9